UPAYA PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG PEMANFAATAN TANAMAN LOKAL SEBAGAI PELANCAR ASI - Sri Handayani; Yopi Suryatim Pratiwi; Nurul Fatmawati; Yadul Ulya; Siskha Maya Herlina; Rosa Ratna Umara (Stikes Yarsi Mataram, 2022)
Infant and toddler mortality rates are still high in Indonesia. The high mortality rate in Indonesia is caused by nutritional factors. Exclusive breastfeeding is able to reduce infant mortality, but the achievement of exclusive breastfeeding is still below the scope. Insufficient milk production is one of the causes of the low achievement of exclusive breastfeeding. In Indonesia, there are many plants that can promote breast milk, but cases of insufficient milk production are still high. The use of local plants as breast milk stimulants must be supported by comprehensive information so that they have a beneficial effect. Therefore, it is necessary to conduct health education on the use of local plants as breast milk promoters. The activity of providing health education on the use of local plants as an effort to increase breast milk production was carried out in Terong Tawah Village, Labuapi District, West Lombok Regency on November 8, 2021 and was attended by 09 respondents. The results of the participants' pretest and posttest showed an increase in knowledge about the use of local plants as an effort to increase breast milk production. After this community service activity, it is expected that pregnant women, especially pregnant women in the third trimester, can begin to apply all the material obtained about the use of local plants as breast milk, as an effort to prepare for breastfeeding.